Non‐carious cervical lesions: influence of morphology and load type on biomechanical behaviour of maxillary incisors. (31st July 2013) - Soares, PV; Santos‐Filho, PCF; Soares, CJ; Faria, VLG; Naves, MF; Michael, JA; Kaidonis, JA; Ranjitkar, S; Townsend, GC
Abstract: Background: The aim of this study was to measure the effect of simulating two different loads on maxillary incisors displaying eight morphological types of non‐carious cervical lesions, unrestored and restored with an adhesive restoration, by quantifying the stress distributions generated using finite element analysis. Methods: Virtual models of maxillary incisors were generated using the CAD software (RhinoCeros). After composing virtual dental and supporting structures with and without non‐carious cervical lesions, each model was meshed using a control mesh device (ANSYS Finite Element Analysis Software). All of the virtual models were subjected to two load types, oblique load and vertical load, to simulate occlusal forces of 100 N each. Comparisons were made between simulated teeth with non‐carious cervical lesions, with and without composite resin restorations, and a simulated sound tooth. Data summarizing the stress distributions were obtained in MPa using von Mises criteria. Results: Oblique loading on simulated non‐carious cervical lesions resulted in greater stress concentration compared with vertical loading, and non‐carious cervical lesions with acute angles displayed higher stress concentrations at the depth of the lesion. Restoring the lesions with an adhesive restoration, such as composite resin, appeared to overcome this stress concentration. Conclusions: Restoring NCCLs with adhesive restorative materials, such as a nanohybrid composite resin, appears to recover the biomechanical behaviour similar to sound teeth.